Memristor Technology: Synthesis and Modeling for Sensing and Security Applications - Abunahla, Heba (Analog Circuits and Signal Processing,, 2018)
This book provides readers with a single-source guide to fabricate, characterize and model memristor devices for sensing applications. The authors describe a correlated, physics-based model to simulate and predict the behavior of devices fabricated with different oxide materials, active layer thickness, and operating temperature. They discuss memristors from various perspectives, including working mechanisms, different synthesis methods, characterization procedures, and device employment in radiation sensing and security applications. Discusses a detailed, physics-based mathematical model, which can guide the design and fabrication process of memristive devices; Describes detailed fabrication process steps for real memristor devices, enabling readers to synthesize similar and enhanced memristor devices; Applies techniques presented to novel applications, including radiation sensing and security.